Single or double layer intestinal anastomosis? - Bhargava, Gopal S.; Singh, Harmandeep; Singh, Jagpreet (International Surgery Journal, 2016)
Background: Intestinal anastomosis after resection or following a palliative stoma formation is a very common procedure in India, being a tropical country and hence a large incidence of intestinal perforations as well as rising incidence of malignancies. Volume of procedure being performed all over India suggested us to try some better method of anastomosis as only a few studies have been conducted till now in this part of the world. Methods: The study was conducted among 84 patients [Double layer (group “A”) and single layer extra mucosalanastomosis (group “B”) groups of 42 patients each] over a period of 2 years. Patients were assigned to either of the groups in a prospective and randomized fashion. Groups were evenly matched by age, sex, diagnosis and location of anastomosis. Patients below 18 and above 60 years age, location of anastomosis other than small bowel and gut wall with oedema, inflammation, ulcers, ischemia, scarring, etc. were excluded from the study. Results: Outcomes as time taken for anastomosis, material cost, anastomotic leak, intra-abdominal abscesses and length of hospital stay were recorded in each group. Time taken and material cost for anastomosis was significantly low in group Bas compared to group A. Postoperative anastomosis leak, intra-abdominal abscess formation and hospital stay, in both the groups, were comparable without significant difference. Conclusions: Single layer extramucosalanastomosis is cost effective and time saving procedure as compared to double layer method without significant difference in postoperative complications.